Fuzzy Dual Numbers Theory and Applications - Mora-Camino, Felix; Nunes Cosenza, Carlos Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This is the first book focusing exclusively on fuzzy dual numbers. In addition to offering a concise guide to their properties, operations and applications, it discusses some of their advantages with regard to classical fuzzy numbers, and describes the most important operations together with a set of interesting applications in e.g. optimization, decision-making and system design. The book provides students, researchers and professionals the necessary theoretical background to apply this particular subset of fuzzy numbers to decision-making problems involving uncertainty. Further, it shows how to solve selected engineering and management problems and includes detailed numerical examples.
Fuzzy Numbers -- Dual Numbers -- Fuzzy Dual Numbers -- Fuzzy Dual Linear Matrix Inequalities -- Fuzzy Estimation of Distribution Matrices -- Fuzzy Dual Entropy and Applications -- Fuzzy Dual Programming.
Keywords: Computational intelligence; Mathematical optimization; Calculus of variations; Operations research; Artificial intelligence; Computational Intelligence; Calculus of Variations and Optimization; Operations Research and Decision Theory; Artificial Intelligence